Regulation of methane gas output from an anaerobic reactor system using moving horizon H∞ control - Yildiz Tascikaraoglu, Fatma; Engin, Seref Naci (Tubitak Scientific & Technological Research Council Turkey, 2015)
In this study, the moving horizon H-infinity control used for tracking a desired methane gas output from an anaerobic wastewater treatment reactor is compared with classical H-infinity control and a proportional-integral-derivative controller. The nonlinear system is first linearized around the set of equilibrium and operating points selected, and then the linear matrix inequalities required to comply with the constraints and guarantee the stability are constructed. Finally, the experimental results are obtained by implementing the control method in a MATLAB environment. It is concluded that moving horizon H-infinity control yields satisfactory results.
Keywords: Anaerobic reactor system; moving horizon H-infinity control; linear matrix inequality; MODEL-PREDICTIVE CONTROL; Computer Science; Engineering